Regionale ökonomische Resilienz: Eine schumpeterianische Perspektive - Simmie, James (Raumforschung und Raumordnung | Spatial Research and Planning, 2014)
This paper takes up the Schumpeterian argument that innovations drive economic recovery following cyclical phases of recession and depression. The performance of the regional innovation systems of two contrasting regions in England is examined in the light of this argument. It is shown that the long-term development of the regions’ respective innovation systems contributed significantly to the long-run adaptation and consequential economic resilience of their economies in the face of periodic external economic shocks. It is also argued that regional innovation systems policies can contribute to the adaptation of regional economies and therefore their economic resilience.
Keywords: Regional resilience; Schumpeterian business cycles; North East and South East England; Regional adaptation